Resolução online de disputas (ODR): regulamentação e utilização pelos tribunais de justiça brasileiros como forma de expansão do acesso à justiça - GOMES, Tunny Tanara da Moda Corrêa (2023)
This paper aims to conduct a study on the use of Online Dispute Resolution (ODR) by the Brazilian Courts of Justice as a way to expand access to justice in the digital era. To understand the topic, that still is little explored in Brazil, a study of the development of online dispute resolution in the country will be carried out, as well as an analysis of normative acts that recognize and regulate the practice.